Effect of Soaking on the Nutritional Values of Kordala (Maerua Pseudopetalosa) Seeds Grown in Kordofan Region, Sudan - Holli, Elrady E Bukhari; Nour, Abdelazim A.M; Ahmed, Adam Ismail (Journal of Food Technology Research, 2017)
The aim of this study is to eliminate the alkaloids from Kordala (Maerua pseudopetalosa) by soaking process and examine their effect on nutritional value, protein digestibility and anti- nutritional factors. The seeds were soaked in water for seven days with water changed daily. The proximate composition, protein digestibility, minerals composition, anti-nutritional factors and amino acids profile were examined. The results obtained showed that soaking decreased protein content (from 21.67 to 11.64 %), ash (from 2.9 to 0.3%), fat (from 1.78 to 1.05%), polyphenols (from 170.82 to 160 mg/100g), phytic acid (from 743.5 to 588.9 mg/100g), minerals and amino acids content also decreased. The process increased moisture content (from 8.3 to 9.62%), fiber content (from 1.36 to 4.27%), total carbohydrates (from 63.99 to 73.12%) and protein digestibility (from 58.4 to 68.1%) for raw and soaked seeds, respectively. Comparing these values with recommended dietary allowances, the results indicated that Kordala (Maerua pseudopetalosa) seeds could be a good supplement source for some nutrients.